Pengaruh Literasi Keuangan, Motivasi Keuangan, Kemajuan Teknologi, Sosial Media Terhadap Minat Investasi Generasi Z - Sari, Shinta Yulita; Wibowo, Purwo Adi (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
This study aims to analyze the influence of financial literacy, financial motivation, technological advances, and social media on the interest in investing in the capital market among Generation Z in Jepara Regency. In this research, a quantitative approach was used with a population of 388.337 Generation Z in Jepara Regency. The sample selection technique used was purposive sampling, and during the research period 100 respondents were obtained. Primary data in this research was obtained through distributing questionnaires, while secondary data consisted of previous research and information that supports the research results. The analysis technique used is multiple linear regression and data processing using SPSS 25. The findings in this research state that the variables of financial literacy, financial motivation, technological progress and social media are proven to have a positive and significant influence on interest in investing in the capital market for Generation Z. in the Jepara Regency with a calculated t value > 1.660 and a significance probability value < 0.05. Generation Z in Jepara Regency shows great interest in investing in the capital market, which is driven by increased understanding of finance, technological advances, and the role of social media in providing information and making it easier to access investment online.